Descripción de los procesos tecnológicos más utilizados en la fabricación de alimentos balanceados y su uso en producción animal - Mastian Sisa, Rosa Mercedes (2025)
Today, the agri-food industry plays an important role in the global economy, providing a wide variety of essential products for human and animal nutrition. Within this context, feed production plays an important role in providing effective feed for poultry, pigs, and cattle, which in turn supports the meat and dairy supply chains. Feed production has enabled the efficient integration of all processes and agents involved in animal production, optimizing the reception and storage of raw materials. The purpose of this research was to determine the most commonly used technological processes in feed manufacturing and their use in animal production. In preparing this document, up-to-date information was compiled, including scientific articles, websites, and virtual libraries that provide authors' opinions and ideas. The research was conducted as a non-experimental bibliographic study, utilizing synthesis, analysis, and summary methods. The findings determined that technological processes in the production of feed for farm animals are very important for optimizing the formulation and subsequently improving the animals' productive performance. Agricultural byproducts can be reused to reduce environmental impact and recover waste. The technological processes used in the production of feed for farm animals include milling, mixing, mashing, pelleting and extrusion, drying, cooling, packaging, and storage. Proper feeding of animals destined for the production of food for human consumption is a key factor in ensuring the quality of the final products. However, producers are constantly seeking alternative feeds that offer good quality at competitive prices, with the goal of improving both the profitability of their farms and the quality of life of consumers.